Search of Fuzzy Periods in the Works of Poetry of Different Authors - Artur Nor; Eugene Korotkov (Advances in Fuzzy Systems)
We applied a new method for the identification of fuzzy periods and the insertion and deletion of characters were taken into consideration while studying the works of poetry. The technique employs genetic algorithm, dynamic programming, and the Monte Carlo method. In the present work, the technique was applied to poems written by the famous Russian and foreign classics. A total of 95 poems were studied; and fuzzy periods possessing high statistical significance were identified with more than half of the poems under study. The existence of correlation between the stressed vowel letters in a poem with the position of the fuzzy periods was shown. The present study shows that a work of poetry contains both semantic component and fuzzy periods of letters; hence a poem could have psychological impact on the audience.